Autism Artisans: Pioneering Neuro-Inclusive Halal Markets - Maspul, Kurniawan Arif; Ardhin, Muhammad (Jurnal Pemberdayaan Ekonomi dan Masyarakat, 2025)
Autism Artisan Cooperatives (AACs) in Malaysia redefine neuro-inclusive prosperity by transforming autistic adults’ sensory strengths into economic and cultural power. Confronting systemic exclusion—fewer than 16% of autistic Malaysians hold stable jobs (Khalid, 2024)—AACs leverage a $680 billion global artisan market (UNESCO, 2021) through halal-certified, sensory-adapted goods like tactile songket textiles and weighted blankets, crafted in SIRIM-compliant workshops. Backed by SME Corp’s e-commerce networks and MHDC’s design mentorship, AACs boosted artisan incomes by 40% in Kelantan (MHDC, 2022), while behavioral “nudges” and AI co-design (ChatGPT) amplify autistic innovation. Strategic alliances with Islamic NGOs slashed employer stigma by 72% (DOSM, 2023), reframing neurodiversity as communal strength (ummah), and halal compliance unlocks a $3.2 trillion global market (State of the Global Islamic Economy, 2022). Outpacing models like India’s Gramshree, AACs merge circular-economy practices (upcycled batik) with Elkington’s triple bottom line, proving that equity and sustainability are mutually catalytic. This blueprint—where cultural heritage, ethical consumerism, and neurodiverse talent converge—charts a scalable path for global resilience, transforming autism from marginalization to market leadership.